Pathomorphological changes in intestinal yersiniosis in cats - Grеgory Zon; Olga Truba; Lyudmila Ivanovskaya; Illia Zon; Roman Petrov (Наукові горизонти, 2022)
Mammalian yersiniosis is of interest to researchers around the world, due to the expansion of the range of spread of the disease. Most publications of previous years concerned productive animals and the spread of the pathogen in environmental objects. Recently, isolated reports have begun to appear about the isolation of pathogens, yersinioses, from unproductive animals and a rather specific course of diseases. The interest of bacteriologists and epidemiologists is based on the increasingly frequent detection of Y. Enterocolitica pathogen in the body of so-called companion animals, which are often directly in close contact with the host. To date, the possibility of human infection from a bacterial carrier has already been proven. The purpose of this study was to clarify the main vectors of pathogenesis of spontaneous feline intestinal yersiniosis by investigating changes in the architectonics of parenchymal organs. The materials for the study were the internal organs of cats that died as a result of spontaneous intestinal yersiniosis, the diagnosis of which was established based on the clinical picture and the determination of diagnostic titres of antibodies to standard yersiniosis antigens. It was found that the feline disease is mostly asymptomatic, and due to the affinity of many pathogens of yersiniosis in animals and humans, it becomes both epizootological and epidemiological in nature. The most significant pathomorphological changes were found in the organs of cats with intestinal yersiniosis; in the organs of the gastrointestinal tract (stagnant phenomena, uneven damage to intestinal villi, sometimes crypts of the submucosal layer and vascular walls, active cell proliferation in desquamation areas); in the liver, mainly protein dystrophy, local areas of necrobiosis and cytolysis of hepatocytes; in the kidneys, congestive hyperaemia and the development of haemorrhagic diathesis, signs of vascular fragility and diapedesis bleeding, and in the case of chronisation of the process – a response to vascular endothelial damage in the form of migration of mononuclears to the future focus of inflammation; in the spleen and lymph nodes, delymphotisation of white pulp was observed, in other cases, an increase in the number of secondary lymph nodes with the formation of large reactive centres was detected in the spleen